Baltasar Pardal Vidal and La Grande Obra de Atocha. (Journal of Parents and Teachers, 2017)
Baltasar Pardal Vidal is a Galician priest who started in La Coruña in 1923 “La Grande Obra de Atocha”. This institution pretends to implement a new Schedule in the educative process, as New School did, they put the centre in the child to get their objective, it requires a determined teacher’s profile.
Keywords: La Grande Obra de Atocha; Baltasar Pardal. Teacher’s book; school; Coruña; great education.